Music Learning Strategies to Develop Students’ Creativity at SMA Negeri 1 Brebes - Jehan Shaila Hafeez; Sunarto Sunarto (Universitas Muhammadiyah Enrekang, 2025)
Creative music learning strategies are essential for developing students’ creativity. One applicable approach is project-based learning, where students are given the opportunity to create their own musical works. One indicator of low student creativity in music learning is their limited ability to write song lyrics. This study is grounded in Elliot W. Eisner’s humanistic art education theory, which emphasizes the importance of self-expression, creativity, the teacher’s role as a facilitator, and qualitative assessment in the arts learning process. The research method employed is a descriptive qualitative approach using techniques such as observation, interviews, documentation, and creative task questionnaires. The results show that the music learning strategies implemented at SMA Negeri 1 Brebes enhance students’ creativity in writing song lyrics through a more structured, project-based, and collaborative approach. By providing students with space to express themselves and by improving their understanding of lyric structure and writing techniques, their creative potential can be more effectively developed. The challenges faced by teachers and students in implementing lyric-writing strategies are mainly related to the availability of facilities and the teacher’s willingness to adapt their teaching approach. These challenges can be addressed more effectively, although limited time and lack of experience remain major constraints.